Eligibility for PCSK-9 inhibitors treatment in acute coronary syndrome, chronic coronary artery disease and outpatient dyslipidemic patients. (June 2020) - Vlachopoulos, Charalambos; Dima, Ioanna; Soulis, Dimitrios; Terentes-Printzios, Dimitrios; Skoumas, Ioannis; Aznaouridis, Konstantinos; Solomou, Eirini; Richter, Dimitrios; Tousoulis, Dimitrios
Abstract: Background and aims: We aimed to investigate potential eligibility for proprotein convertase subtilisin–kexin type 9 (PCSK9) inhibitors in patients with coronary artery disease and dyslipidaemia according to patient characteristics and variable criteria. Methods: We prospectively enrolled 2000 patients (acute coronary syndrome = 407, chronic coronary artery disease inpatients = 1087, outpatient Lipid's clinic = 506). To calculate PCSK-9 inhibitors real-world eligibility, a proprietary adjustable software was developed, which stores data and patient characteristics and can determine eligibility depending on different criteria. We tested four scenarios with different LDL thresholds according to ESC/EAS 2016 and 2019 Guidelines, 2017 American College of Cardiology Expert Consensus, and National criteria. Results: The eligible percentage was 18.85%, 9.75%, 8.55% and 2.15%, in the total population for the four classifications, respectively, and it varied according to clinical status. The increase toward more recent guidelines was mostly attributed to the increasing number of coronary patients who become eligible as our criteria become stricter. Conclusions: For the first time, a realistic estimation of PCSK-9 eligibility is provided via an adjustable predictive model in a population of 2000 patients with acute coronary syndrome, chronic coronary artery disease and dyslipidaemia. This can be a valuable tool for the incorporation of PCSK-9 inhibitors in health care systems. Graphical abstract: Image 1 Highlights: Eligibility for proprotein convertase subtilisin–kexin type 9 (PCSK9) inhibitors. Adjustable predictive model software. Coronary artery disease patients. Familial hypercholesterolaemia patients.